PENINGKATAN HASIL BELAJAR SISWA SMK NEGERI 1 SERIRIT DENGAN MODEL PEMBELAJARAN DISCOVERY-INQUIRY - I Nyoman Winaya (Purwadita : Jurnal Agama dan Budaya, 2018)
This classroom action research was conducted at SMK Negeri 1 Seririt in class XIAkutansi 1 whose students’ ability for linear program material is quite low. The purpose of thisclass action research is to know the improvement of student learning result in Linear Programcompetence in class XI Accounting 1 SMK Negeri 1 Seririt through the implementation of LKSassisted Discovery-Inquiry model. Data collection methods are observations and testsAchievement learning, data analysis methods are descriptive for both qualitative data and forquantitative data. The results obtained from this study is Discovery_Inquiry learning model canimprove learning achievement. This is evident from the results obtained in the first cycle averageof 72.63 for learning outcomes with 64.52% classical completeness. and the result obtained incycle II average is 77,82 for learning result with 100% classical completeness. From cycle I tocycle II increased 5.20 points for the results of learning and classical completeness increased35.48%. Based on this Model Learning Discovery-Inquiry LKS assisted to improve studentachievement class XI Accounting 1 SMK Negeri 1 Seririt year lesson 2017/2018.Keywords: Discovery-Inquiry Model Learning, LKS, Student Learning Results